Directional Magnetization Reversal Enables Ultrahigh Energy Density in Gradient Nanostructures. Issue 36 (26th July 2021) - Lou, Li; Li, Yuqing; Li, Xiaohong; Li, Hailing; Li, Wei; Hua, Yingxin; Xia, Weixing; Zhao, Zhihe; Zhang, Haitian; Yue, Ming; Zhang, Xiangyi
Abstract: High‐performance ferromagnetic materials are essential for energy conversion and electronic devices. However, the random and nonuniform magnetization reversal in ferromagnetics limits their performance that can be achieved. Here, through both micromagnetism simulations and experiments, a directional magnetization reversal that initiates first from large grains toward smaller ones is discovered by engineering Nd2 Fe14 B/α‐Fe gradient nanostructures. Such directional magnetization reversal enables a rare combination of high magnetization and large coercivity, thus leading to a record‐high energy density (26 MG Oe) for isotropic permanent magnetic materials, which is ≈50% higher than that of its gradient‐free counterpart. The unusual magnetization reversal originates from an ordered arrangement of grain sizes in the gradient material, where the large grains have a lower reversal field than that of the smaller ones. These findings open up new opportunities for developing high‐performance magnetic materials. Abstract : A directional magnetization reversal is discovered by engineering Nd2 Fe14 B/α‐Fe gradient nanostructures, in contrast to the conventional random and nonuniform magnetization reversal in ferromagnetics. This directional magnetization reversal enables a rare combination of high saturation magnetization and high coercivity, thus leading to a record‐high energy product of 26 MG Oe for isotropic permanent magnetic materials.